2015
DOI: 10.1111/bjd.14054
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly-growing squamous cell carcinoma shortly after treatment with ingenol mebutate for actinic keratoses: report of two cases

Abstract: Actinic keratoses (AKs) are defined as cutaneous areas of atypical squamous transformation that are regarded as an early step in the continuum of alterations leading from normal skin to invasive and metastatic squamous cell carcinoma (SCC). AKs are classified as precancerous lesions by some authors and in situ SCC by others. The rate of evolution of a given AK to an invasive SCC has been estimated as 0·075-0·096% per lesion per year. These rates are similar to those estimated for gynaecological intraepithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…In addition, clinical cases of rapid progression of AK to invasive SCC after treatment with IM have been reported. 10 These data are in line, although indirectly, with results of our study and allow us to hypothesize that the IM gel does not act on AK-MSCs that may be the real responsible of the onset and development of the lesions. Future therapeutic strategies could be directed to the eradication of MSCs of AKs, considering their peculiar cytokinetic and relationship with the tissue niche.…”
supporting
confidence: 90%
“…In addition, clinical cases of rapid progression of AK to invasive SCC after treatment with IM have been reported. 10 These data are in line, although indirectly, with results of our study and allow us to hypothesize that the IM gel does not act on AK-MSCs that may be the real responsible of the onset and development of the lesions. Future therapeutic strategies could be directed to the eradication of MSCs of AKs, considering their peculiar cytokinetic and relationship with the tissue niche.…”
supporting
confidence: 90%
“…A biomarker that can stratify the risk of transformation of AK into SCC has still not been identified. Furthermore, the field directed therapies used to reduce this risk [17], have demonstrated inducement of carcinogenesis in the field treated [18,19,20]. Therefore, dermatologists need to be able to select the treatment and the risk-patients towards a personal medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the activation of EGFR induces stimulation of ERK, with consequent overexpression of cyclin D1, which is frequently involved in keratinocyte carcinogenesis [ 108 ]. In this regard, Moreno Romero et al reported two cases of rapidly growing squamous cell carcinoma after treatment of ingenol mebutate for AKs on the forehead (time to onset: 4 weeks) and the neck (time to onset: 5 weeks), and proposed that, in some cases, the inflammatory process induced by ingenol mebutate could accelerate the transformation of AKs into SCCs [ 109 ]. It is interesting to highlight that the MAPK/ERK signal pathway is involved also in the mechanism of action of ingenol mebutate and could explain, at least in part, this paradoxical response, which consists of reduction of cell viability and proliferation, and, on the other hand, promotion of tumor cell growth [ 110 ].…”
Section: Late Onset Side Effectsmentioning
confidence: 99%